Outcomes from Converting HL7 v2.x Tables to Codesystems and Value Sets (Represented in FHIR)...36th Medical Informatics Europe (MIE) Conference, May 25-28, 2026, Genoa, Italy. - OEMIG, Frank (Studies in Health Technology & Informatics, 2026)
Introduction: Legacy standards like HL7 version 2.x historically maintain vocabulary in form of simple tables with table values which has been improved over the years. But it is still lacking a lot of problems and providing inconsistencies if the content is to be converted into FHIR codesystems and value sets. This paper summarizes the findings from the HL7 v2 tables project (2010-2017) with the addition of migrating the tables to FHIR CodeSystem and ValueSet considering semantic versioning across all v2 versions. Methods: The vocabulary content is available in form of a database so that SQL in combination with PHP scripting can be used to investigate and analyse the content. Results: The investigation of the vocabulary content has revealed a lot of foundational errors being made during maintenance. These are provided in this paper to avoid future mismanagement. Conclusion/Discussion: The improved vocabulary fixing the mentioned problems must be made normative to take effect.